A Framework for Robust Address Assignment in WSNs Whispering to Avoid Intruders. (25th September 2013) - Ribeiro, Carlos; Anastácio, Ivo; Costa, André; Baptista, Marcia
Wireless sensor networks (WSNs) are becoming bigger, and with this growth comes the need for new automatic mechanisms for initializations done by hand. One of those mechanisms is the assignment of addresses to nodes. Several solutions were already proposed for mobile ad hoc networks but they either (i) do not scale well for WSN; (ii) have no energy constraints; (iii) have no security considerations; (iv) or have no mechanisms to handle fusion of network partitions. We proposed an address self-assignment protocol which uses negative acknowledgements and an improved version of a flood control mechanism to minimize the energy spent; uses a technique named whispering to achieve robustness against malicious nodes; is able to detect dynamic network re-joint and dynamic node addition without exchanging specific messages; and handles both dynamic events without compromising routing tables.